Can randomized controlled trials be conducted in community social service settings?. Issue 5 (May 2015) - Lam, T.H.; Stewart, S.M.; Hirschmann, M.R.; Fabrizio, C.S.; Yu, N.X.
Highlights Results of five community-academic randomized trials have been shared. Challenges included the need for controls, briefness of sessions, and participant recruitment. The partnership built community capacity and generalized new evidence.